Nano-Oncologic Vaccine for Boosting Cancer Immunotherapy: The Horizons in Cancer Treatment - Chao Chen; Yue Xu; Hui Meng; Hongyi Bao; Yong Hu; Chunjian Li; Donglin Xia (Nanomaterials)
Nano-oncologic vaccines represent a groundbreaking approach in the field of cancer immunotherapy, leveraging the unique advantages of nanotechnology to enhance the effectiveness and specificity of cancer treatments. These vaccines utilize nanoscale carriers to deliver tumor-associated antigens and immunostimulatory adjuvants, facilitating targeted immune activation and promoting robust antitumor responses. By improving antigen presentation and localizing immune activation within the tumor microenvironment, nano-oncologic vaccines can significantly increase the efficacy of cancer immunotherapy, particularly when combined with other treatment modalities. This review highlights the mechanisms through which nano-oncologic vaccines operate, their potential to overcome existing limitations in cancer treatment, and ongoing advancements in design. Additionally, it discusses the targeted delivery approach, such as EPR effects, pH response, ultrasonic response, and magnetic response. The combination therapy effects with photothermal therapy, radiotherapy, or immune checkpoint inhibitors are also discussed. Overall, nano-oncologic vaccines hold great promise for changing the landscape of cancer treatment and advancing personalized medicine, paving the way for more effective therapeutic strategies tailored to individual patient needs.